2020
DOI: 10.1302/0301-620x.102b7.bjj-2019-1633.r1
|View full text |Cite
|
Sign up to set email alerts
|

2020 Otto Aufranc Award: Malseating of modular dual mobility liners

Abstract: Aims This combined clinical and in vitro study aimed to determine the incidence of liner malseating in modular dual mobility (MDM) constructs in primary total hip arthroplasties (THAs) from a large volume arthroplasty centre, and determine whether malseating increases the potential for fretting and corrosion at the modular metal interface in malseated MDM constructs using a simulated corrosion chamber. Methods For the clinical arm of the study, observers independently reviewed postoperative radiographs of 551 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 19 publications
5
55
0
1
Order By: Relevance
“…As a result, size of the dual-mobility head is smaller in Trident than in the 1-piece cup DMC designs. The Trident has also been associated with a risk of mal-insertion of the liner (Langdown et al 2007, Romero et al 2020. The "DMC Trident group" included all Trident DMCs (n = 399), and the "DMC Others group" (n = 263) included the rest of the DMCs.…”
Section: Statisticsmentioning
confidence: 99%
“…As a result, size of the dual-mobility head is smaller in Trident than in the 1-piece cup DMC designs. The Trident has also been associated with a risk of mal-insertion of the liner (Langdown et al 2007, Romero et al 2020. The "DMC Trident group" included all Trident DMCs (n = 399), and the "DMC Others group" (n = 263) included the rest of the DMCs.…”
Section: Statisticsmentioning
confidence: 99%
“…Screening by title and abstract excluded a further 21, leaving 32 articles which underwent full-text review. Out of these, 16 were identified for overall inclusion 16 - 31 ( Fig. 1 32 ), with meta-analysis performed on specific subsets as described below.…”
Section: Resultsmentioning
confidence: 99%
“…Another theory is provided by the radiographic study of 551 cases, finding that 5.8% of MDM liners were malseated on retrospective evaluation. 31 Subsequent in vitro modelling in the same study suggested that liner malseating can lead to lower fretting onset loads. Taken together, these results corroborate findings by Kolz et al 30 describing three different patterns of wear, and suggest that debris generation in MDM constructs is likely a combination of intrinsic (component design) and extrinsic (surgical) factors.…”
Section: Discussionmentioning
confidence: 96%
“…Otherwise, the incidence of the problem may have been higher and corroborating studies are needed in this regard. By comparison, we are aware of one study that demonstrated an incidence of MDM liner malseating of 5.8% in a cohort of patients who underwent THA, in which the surgery was performed by 17 surgeons, where routine liner testing was not performed [ 18 ]. Furthermore, it was previously noted by Miller et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, added modularity introduces additional potential complications, including modular liner malseating and/or dissociation and intraprosthetic dislocation (IPD) [ 16 , 17 ]. The notion that a stiff cobalt-chrome liner has a potentially higher risk of malseating because of less-conforming tolerance than that of polyethylene is supported by experiences with incomplete seating of the liner with metal-backed ceramic liners [ 18 , 19 ]. However, there is a paucity of data on modular dual-mobility (MDM) liners incompletely seating, any untoward consequences, and how to minimize and manage the occurrence [ 20 ].…”
Section: Introductionmentioning
confidence: 99%